Optimizing the Role of Digital Marketing through Digital Road trip to Acceleration Tajuk Tourism Village Pilot Projects: Optimalisasi Peran Digital Marketing melalui Digital Roadtrip Dalam Rangka Mendorong Akselerasi Rintisan Desa Wisata Tajuk - Hawik Ervina Indiworo; Efriyani Sumastuti; Dhea Rizky Amelia (Mattawang: Jurnal Pengabdian Masyarakat, 2022)
Digital Marketing is needed to encourage the acceleration of the Tajuk Tourism Village Pioneer. By using a digital roadtrip model through Instagram, it turns out to be able to promote tourism potential in Tajuk Village, because its main feature is that it features images and videos, so that Instagram users feel they are in the Tajuk Village Tourism Area. Training activities on the use of digital marketing are carried out for young people, as the largest proportion of active Instagram users. With the training carried out, the Tajuk Village youth group can independently design Instagram content for promotional purposes. In the context of accelerating the Pioneer of the Tajuk Tourism Village, a comprehensive synergy is needed from all levels of society. The trick is to encourage active Instagram users in Tajuk Village to follow "Getasan Tourism Village Instagram," and share every moment when doing tourist activities. This is consistent with previous findings that people in the era of social media not only act as recipients of information, but also as information givers. The content created is expected to be useful for tourists in their decision making. Abstrak Digital Marketing diperlukan untuk mendorong akselerasi Rintisan Desa Wisata Tajuk. Dengan menggunakan model digital roadtrip melalui Instagram, ternyata mampu untuk mempromosikan potensi wisata di Desa Tajuk, karena fitur utamanya yang mengunggulkan gambar dan video, sehingga pengguna Instagram merasa berada di Kawasan Wisata Desa Tajuk. Kegiatan pelatihan pemanfaatan digital marketing dilakukan kepada penduduk usia muda, sebagai proporsi terbesar pengguna aktif Instagram. Dengan pelatihan yang dilaksanakan, kelompok pemuda Desa Tajuk dapat secara mandiri merancang konten Instagram untuk tujuan promosi. Dalam rangka akselerasi Rintisan Desa Wisata Tajuk, diperlukan sinergi yang menyeluruh dari semua lapisan Masyarakat. Caranya dengan mendorong pengguna aktif Instagram di Desa Tajuk untuk mengikuti “Instagram Desa Wisata Getasan,” dan membagikan setiap momen ketika melakukan aktivitas wisata. Hal ini sesuai dengan temuan sebelumnya bahwa orang-orang di era media sosial tidak hanya berperan sebagai penerima informasi, tetapi juga sebagai pemberi informasi. Konten yang dibuat digharapkan bermanfaat bagi wisatawan dalam pengambilan keputusan mereka.